PO79 | Trying to hit the hit in the shadow of renal failure: a complex case managed with danaparoid (Bleeding, Thrombosis and Vascular Biology)
Background: Heparin-induced thrombocytopenia (HIT) type II is a rare, immune-mediated adverse effect of heparin exposure, caused by antibodies against PF4-heparin complexes. These trigger platelet activation and can lead to life-threatening thrombosis. Managing HIT is challenging: anticoagulation is mandatory despite thrombocytopenia. In hemodialysis patients, who are frequently exposed to heparin and have limited alternatives due to renal clearance, clinical decisions are often complex. Early recognition is key to avoiding complications.